2012
DOI: 10.1099/ijs.0.027771-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus kochii sp. nov., isolated from foods and a pharmaceuticals manufacturing site

Abstract: Three Gram-staining-positive, strictly aerobic, motile, catalase-positive, endospore-forming rods, designated WCC 4582 T , WCC 4581 and WCC 4583, were isolated from two different food sources and a pharmaceuticals production site. The three isolates were highly similar in their 16S rRNA gene sequences (100 % similarity) and groEL sequences (99.2-100 % similarity), Fouriertransform infrared spectroscopic fingerprints and other features tested. The isolates were most closely related to Bacillus horneckiae; the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…However, the significant growth‐promoting effect on tomatoes was not observed in our study. B. kochii was isolated previously from food, and B. oceanisediminis was isolated from marine sediment in a previous study, but prior to this study these bacteria had not been evaluated against Meloidogyne spp. Both strains are widespread and here, for the first time, their nematicidal activity is confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the significant growth‐promoting effect on tomatoes was not observed in our study. B. kochii was isolated previously from food, and B. oceanisediminis was isolated from marine sediment in a previous study, but prior to this study these bacteria had not been evaluated against Meloidogyne spp. Both strains are widespread and here, for the first time, their nematicidal activity is confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…This also accords with previous research, which showed that B. Paramycoides from Thai prawn paste has lipase activity of 22 U.mL -1 (Daroonpunt et al 2019). B. kochiiwas only reported by Seiler et al (2012) as producing fatty acids from esterase lipase (C8) process. However, the result of lipaseproducing ability of B. kochii has not previously been described.…”
Section: Discussionmentioning
confidence: 99%
“…The Bacillus genus represents one of the oldest, most ubiquitous, and molecularly well-characterized bacterial clades. Bacillus kochii , first described in 2012, is aerobic, motile, and catalase positive ( 1 ). This report describes the first complete sequence of B. kochii Oregon-R-modENCODE strain BDGP4, associated with a sequenced Drosophila melanogaster host facilitating mechanistic studies of host–microbiome interactions.…”
Section: Genome Announcementmentioning
confidence: 99%